Features of using the problem teaching methods in psychological and pedagogical training of future teachers of professional and technical educational institutions - Kryvylova, Olena (ScienceRise: Pedagogical Education, 2017)
The article theoretically grounds the influence of problem teaching methods (problem-informational, partially searching, research ones) on the results of psychological-pedagogical training of future teachers of professional-technical educational institutions within pedagogical process (learning, upbringing, development); within general and professional competences; within psychological-pedagogical competence. The problem teaching (creation of problem situation due to the skillful use of questions) attracts interest and active reaction of students, involves attention, helps to start teaching conversation and supports the thoughts exchange, reveals true feelings and views, exposes false ideas. This all favors the rational mastering of future professional activity. The partially searching method (use of pedagogical problems) plays a great role in formation of pedagogical activity experience (projecting, creation and solution of pedagogical situations). The research method (laboratory works, course projects and out-auditory individual learning-research work within disciplines of psychological-pedagogical training cycle) favors systematization, generalization, fixation and practical application of knowledge of learning courses, improvement of skills of independent learning-cognitive activity, visual reflection of the results of searching work. It was revealed, that the offered methods of formation of psychological-pedagogical competence in the process of psychological-pedagogical training favor the gradual increase of acquired learning achievements of future teachers of professional-technical educational institutions, provide the transfer of quantitative knowledge accumulation in the new quality – mastering of competences